A New Method of Mix Design for Cold Patching Asphalt Mixture - Lv, Songtao; Wang, Shuangshuang; Xia, Chengdong; Liu, Chaochao (Frontiers in Materials, 2020)
The objective of this research was to improve the scientificity of designing method of the cold patching asphalt mixture (CPAM). Firstly, the curing temperature of CPAM was studied. In addition, based on the traditional Marshall mix design method, the volume parameters of CPAM were converted, and the low-temperature workability index was added. This is the modified Marshall mix design method to determine the optimal asphalt aggregate ratio of CPAM. Then the initial strength, forming strength, storage stability, water stability and high-temperature stability of CPAM were tested. The properties of CPAM designed by using modified Marshall mix design method were compared with that of CPAM designed by using traditional Marshall mix design method and empirical formula method. The test results show that, the optimal asphalt aggregate ratio of CPAM is 5.38%. 90℃ is recommended for the oven curing temperature of the CPAM specimen. The initial strength and forming strength of CPAM meet the requirements, and the forming strength can reach about twice of the initial strength. The stability of CPAM increases with the increase of storage time. High-temperature performance is good. These properties of CPAM designed by using modified Marshall mix design method were all superior to those of the CPAM designed by using traditional Marshall mix design method and empirical formula method. And the water stability is similar to the CPAM designed by the traditional Marshall mix design method. The CPAM designed by using modified Marshall mix design method shows better road performances, which shows that modified procedure in this study is feasible and can be recommended as the mix design method of CPAM.